2017
DOI: 10.15171/ehem.2017.33
|View full text |Cite
|
Sign up to set email alerts
|

Application of nano- and micro-sized particles of cattle manure on soybean growth

Abstract: Background: Cattle manure (CM) is the most common organic fertilizer used by farmers. However, its usually slow decomposition leads to the use of chemical fertilizers. Therefore, experiments on nano-and micro-sized particles of CM were conducted to evaluate the possibility of accelerating its decomposition in soil. Methods: The effects of a sole application of CM in different sizes (nano-, micro-, and natural-sized particles) in two ranges (5 and 20 Mg ha -1 ) and the combined application of CM and chemical fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
4
3
0
Order By: Relevance
“…These results were true in the first and second seasons. These results were in agreement with that found by Ni et al, (2009), Ekinci et al, (2014), Liu and Lal (2014), Aryanpour et al, (2017); Merghany et al, (2019) and Gosavi et al, (2017) who stated that the positive effect of foliar applied nitrogen, phosphorus, and potassium to sustain proper leaf nutrition as well as carbon balance, and improving photosynthetic capacity is well established.…”
Section: Nono Npk L/fedsupporting
confidence: 92%
“…These results were true in the first and second seasons. These results were in agreement with that found by Ni et al, (2009), Ekinci et al, (2014), Liu and Lal (2014), Aryanpour et al, (2017); Merghany et al, (2019) and Gosavi et al, (2017) who stated that the positive effect of foliar applied nitrogen, phosphorus, and potassium to sustain proper leaf nutrition as well as carbon balance, and improving photosynthetic capacity is well established.…”
Section: Nono Npk L/fedsupporting
confidence: 92%
“…While, the lowest values for this trait (9.056 and 8.873) were obtained from control treatment (without injection) in the first and second season, respectively. These results were in agreement with that found by Liu and Lal (2014); Aryanpour et al, (2017); Gosavi et al, (2017);and Merghany et al, (2019) who stated that the positive effect of foliar applied nitrogen, phosphorus, and potassium to sustain proper leaf nutrition as well as carbon balance, and improving photosynthetic capacity is well established.…”
Section: A 2 No Of Leaves Plant -1supporting
confidence: 92%
“…The CMS 3 has more ability for retention of such as P and K. The partition coefficient was 1.8 L/kg for P and 8.12 L/kg for K, indicated that K is more binding on such materials than N and P. The results indicated that optimum size of manure is 0.8-0.4 mm; it has maximum sorption of both K and P because of their high reactivity due to the large surface to volume ratio leading to improve efficiency of nutrient adsorption. These results were in agreement with (Aryanpour et al, 2017). The maximum sorption of N occurred on CMS 2.…”
Section: Batch Sorption Of Different Particle Sizes Of Manuresupporting
confidence: 91%
“…Perhaps this was due to improving the nutrient availability, nutrient holding capacity of soils, microorganism activity which effect of plant growth in sandy soils (Masarirambi et al, 2010;Mahmoud et al, 2013;Wendimu, 2016). The increase in fresh weight, dry weight and number of leaf yield might be due to that cattle manure in small particle sizes has a less half-life in soil (Aryanpour et al, 2017).…”
Section: Effects Of Different Particle Sizes Of Manure On Fresh Weighmentioning
confidence: 99%